Pediatric Renovascular Hypertension: Diagnosis and Management - Minhas, Kishore; Cahill, Anne Marie; Patel, Premal A. (Seminars in Interventional Radiology, 2025)
Pediatric renovascular hypertension (RVH) is a significant cause of secondary hypertension in children, often resulting from renal artery stenosis (RAS) due to nonatherosclerotic etiologies such as fibromuscular dysplasia (FMD), mid aortic syndrome (MAS), and syndromic conditions like neurofibromatosis type 1 (NF-1). Early diagnosis is critical to prevent long-term complications, including renal dysfunction and cardiovascular disease. Diagnostic evaluation begins with ultrasound, which, despite its limitations, remains the first-line modality. Advanced imaging techniques such as CT angiography (CTA), MR angiography (MRA), and digital subtraction angiography (DSA) provide detailed vascular assessment, with DSA considered the gold standard. Adjunctive tools like intravascular pressure measurements, intravascular imaging, and renal vein renin sampling supplement DSA. Management should have multidisciplinary consensus and is tailored to the individual patient. Pharmacological therapy is seldom sufficient and percutaneous transluminal angioplasty is effective in many cases. Stent placement and surgical interventions are reserved for refractory or complex cases. Chemical ablation in select cases and emerging therapies such as renal denervation offer additional options. This review outlines the current diagnostic and therapeutic approaches to pediatric RVH, emphasizing the importance of personalized care and the role of specialist pediatric centers, with experience in managing RVH, in optimizing outcomes.
Keywords: renal artery stenosis; fibro-muscular dysplasia; mid-aortic syndrome